Social cognition in a case of amnesia with neurodevelopmental mechanisms - Markowitsch, Hans J.; Staniloiu, Angelica; Woermann, Friedrich; Borsutzky, Sabine (Frontiers in Psychology, 2013)
Episodic-autobiographical memory (EAM) is considered to emerge gradually in concert with the development of other cognitive abilities. Developmental studies have emphasized socio-cultural-linguistic mechanisms that may be unique to the development of EAM. Furthermore it was hypothesized that one of the main functions of EAM is the social one. In the research field, the link between EAM and social cognition remains however debated. Herein we aim to bring new insights into the relation between EAM and social information processing (including social cognition) by describing a young adult patient with amnesia with neurodevelopmental mechanisms due to perinatal complications accompanied by hypoxia. The patient was investigated medically, psychiatrically and with neuropsychological and neuroimaging methods. Structural high resolution MRI revealed significant bilateral hippocampal atrophy as well as indices for degeneration in the amygdalae, basal ganglia and thalamus, when a less conservative threshold was applied. In addition to extensive memory investigations and testing other (non-social) cognitive functions, we employed a broad range of tests that assessed social information processing (social perception, social cognition, social regulation). Our results point to both preserved (empathy, core theory of mind functions, visual affect selection and discrimination, affective prosody discrimination) and impaired domains of social information processing (incongruent affective prosody processing, complex social judgments). They support proposals for a role of the hippocampal formation in processing more complex social information that likely requires multimodal relational handling.